Konstruksi Pesan Kesehatan Mental pada Media sosial Studi Kasus Konten Akun Instagram @bounceback.id - Annisa Ghina Fatina (Mahesa Research Center, 2024)
Social media offers an alternative to be a positive forum for its use, especially Instagram where it is used even for a stigmatized subject such as mental health. This research raises the topic of mental health which is constructed in writing and visually on the Instagram account @bounceback.id. Techniques for composing messages on social media are used as a framework for thinking in this research. This research methodology uses a qualitative approach and a constructivist paradigm. The research object in this study is Instagram @bounceback.id, while the research subjects are the people involved in creating messages on Instagram @bounceback.id, namely 3 founders with backgrounds as psychology practitioners. Data collection techniques were carried out using in-depth interviews with research subjects, observing Instagram content, and literature study. Data analysis techniques will be carried out using thematic analysis through open coding, axial coding, and selective coding. The results of this research show that the content preparation strategy from @bounceback.id uses planned strategic communication to achieve its goal of constructing messages about mental. This strategy includes choosing topics that are close to everyday life, choosing pastel colors that create a calm impression, and using popular diction, simple and easy for the audience to understand.